Natural Phenomena in Malay Pantun (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
Numerous natural phenomena are associated with the sea, such as storms, winds, waves, hurricanes, stars, tides, tornadoes, and currents. This is strongly linked to the substantial Malay world on maritime matters. As a result, there is a wealth of evidence for natural phenomena in the pantun. Pantun is not merely a form for amusement, a joke, satire, or something presented in a wedding ceremony; it contains a wealth of philosophy and thoughts. Past research on Malay pantun have primarily focused on flora and fauna found in pantun. This article aims to categorise the natural phenomena that occur in the ocean and characterise the meaning of the pantun based on the inquisitive semantic approach developed in the area of semantics. To achieve the said objective, this study identified 77 pantun found in the book titled Kurik Kundi Merah Saga: Kumpulan Pantun Lisan Melayu, which contains lexical references to natural phenomena in the ocean. The findings of this study indicate that the Malay community in the past used pantun to analogize the environment (natural phenomena) to human life. Such natural phenomena were used as metaphors in pantun to mark the observations and experiences of the Malay community in the past. Through a multidisciplinary study, the aspects of natural phenomena were used to uncover Malay philosophy and the Malay mind hidden within the pantun. The making of pantun is not arbitrary; it is embedded in Malay philosophy and the Malay mind.